Effects of interdisciplinary therapy on reducing ultra-processed food consumption and its impact on cardiometabolic risks factor in women with obesity - Farias, Gisele; K. Shiba, Carolina; D. M. Netto, Bárbara; I. de Oliveira, Gabriela; P. Machado, Paola; O. Rhein, Samantha; M. Oyama, Lila; Thivel, David; M. S. Campos, Raquel; R. Dâmaso, Ana (Seven Editora, 2023)
The prevalence of obesity has grown at an epidemic rate in recent years. According to the World Health Organization (WHO), there are more than 1.9 billion overweight adults, and of these, more than 600 million are classified as being obese, which is equivalent to more than 13% of the world population (1). Obesity is a chronic disease, characterized by the presence of low-grade inflammation, which contributes to the development of other comorbidities including type 2 diabetes mellitus, cardiovascular diseases, non-alcoholic fatty liver disease, and different types of cancer (2).DOI: https://doi.org/10.56238/devopinterscie-109